2020
DOI: 10.1088/1757-899x/849/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Critical green road criteria for Malaysia green rural road index

Abstract: Malaysia is on its path in adapting the green roadway system. The introduction of green road rating tools such as Malaysia Green Highway Index (MyGHI) for highways and Penarafan Hijau (pHJKR Jalan) for non-toll roads which the value of the projects are more than RM50 million are parts of the green initiatives taken towards the sustainable development in Malaysia. However, there is no specific green road rating tool focusing on rural roads in Malaysia. The rural road falls under the state road category, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Revitalize urban areas and attract tourism and improve residents' quality of life [15]. By focusing on environmentally-friendly practices, Bhutan strives to minimize the ecological impact of road construction and maintenance.…”
Section: Green Road Development As a Sustainable Solutionmentioning
confidence: 99%
“…Revitalize urban areas and attract tourism and improve residents' quality of life [15]. By focusing on environmentally-friendly practices, Bhutan strives to minimize the ecological impact of road construction and maintenance.…”
Section: Green Road Development As a Sustainable Solutionmentioning
confidence: 99%
“…The main criteria will decide the primary construction work for rural road development. The criteria are listed based on Adzar et al [6], Abd Rashid et al [7] and Adzar et al [8].…”
Section: Green Rural Road Criteriamentioning
confidence: 99%
“…Current records indicated that a few research had used pHJKR rating tool benchmarking for road and highway. Abd Rashid et al (2020) had used pHJKR rating tool in developing Malaysia Green Rural Road Index (MyGreen RRI) by comparing all components with others green road national rating tool. Meanwhile, research by Adzar et al (2019) focused on sustainability performance during operation and maintenance application.…”
Section: Phjkr Assessment Toolmentioning
confidence: 99%